Amyloid solutions: lecanemab, gantenerumab, and donanemab in the treatment of Alzheimer's disease - Taha basit Ameen; Umair Ali; Omme Salma; Muhammad Abdul Samee; Syed Muhammad Iraj Abbas; Syeda Naveera Kashif; Muhammad Arif Arifi; Mashooque Ali; Maher Khowaja; Syed Muhammad Sinaan Ali; Abdul Raheem (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Alzheimer’s disease (AD), the leading cause of dementia, is a multifaceted neurodegenerative disorder characterized by amyloid-beta (Aβ) aggregation, tau pathology, and neuroinflammation. Recent advances in immunotherapy have yielded monoclonal antibodies (mAbs) with unprecedented precision in targeting Aβ species, offering hope for altering the disease trajectory. Lecanemab’s selective affinity for protofibrillar Aβ disrupts early neurotoxic aggregates, providing a proactive approach for mitigating synaptic dysfunction. Donanemab, by targeting pyroglutamate-modified plaques, combines high specificity with microglial-mediated clearance, while gantenerumab enhances Fc receptor-mediated phagocytosis of both soluble and fibrillar Aβ. These therapies represent a shift from symptomatic treatment to disease modification, reducing the Aβ burden and slowing cognitive decline. However, challenges, such as amyloid-related imaging abnormalities (ARIA), underscore the complexity of balancing efficacy and safety. This review explores the transformative potential of these therapies and contextualizes their mechanisms within the evolving understanding of AD pathophysiology. This highlights the interplay between immune modulation, neuroprotection, and personalized medicine, highlighting the need for future innovations in tackling one of the most formidable challenges in neurology.